Pengaruh Tingkat Kepatuhan, Pemeriksaan Pajak, Penerbitan Surat Ketetapan Pajak, Dan Sanksi Perpajakan Terhadap Peningkatan Penerimaan Pajak Penghasilan Wajib Pajak Orang Pribadi Di KPP PRATAMA MEDAN BARAT - Jessi Charina Sembiring; Seli Pebiola Br Ginting; Willy Ivandy; Herman Herman; Meri Arthanty Zebua (Politeknik Ganesha Medan, 2022)
These indicators include compliance levels, tax audits, assessment letters taxes, and fines. Individual Taxpayers at KPP Pratama Medan Barat are asked to: participate in this research. Individual taxpayer income tax collection growing due to greater compliance, compliance and compliance with regulations taxation. Tax audit has a significant positive impact on tax revenue personal income, Sourced from Tax Foundation research. Tax assessments can increase taxpayer compliance and income when the Directorate General of Taxes send it together with the collection of income tax. Taxpayers who receiving tax sanctions does not violate the law. The sample includes 428,276 taxpayers and taken at random. Test results have a good impact on taxpayer acceptance personal income, either concurrently or partially. Research result shows that taxpayer compliance, tax assessment letters, sanctions taxation, and increasing income tax revenue for individual taxpayers positive and substantial impact on income tax receipts of individual taxpayers personally at KPP Pratama Medan Barat.